2019
DOI: 10.14336/ad.2018.0929
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Links between White Matter Hyperintensity and Medial Temporal Atrophy Reveal Impairment of Executive Functions

Abstract: Although several studies have demonstrated correlation between white matter hyperintensities (WMH) and impairment of executive functions, the underlying anatomical-functional relationships are not fully understood. The present study sought to investigate the correlations between the volume of WMH and medial temporal lobe atrophy (MTA) using quantitative magnetic resonance image (MRI) and a variety of executive function assessments. A total of 91 patients ranging in age from 58 to 90 years with mild cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…PVWMH linked to atrophic processes was likely to affect the long association fibers that connected the more distant cortical areas. The study involving executive functions revealed the association between PVWMH and working memory, DWMH and inhibition performance, and MTA and flexibility performance (32). The relationship between WMH and attention and executive function was also demonstrated in our study.…”
Section: Discussionsupporting
confidence: 80%
“…PVWMH linked to atrophic processes was likely to affect the long association fibers that connected the more distant cortical areas. The study involving executive functions revealed the association between PVWMH and working memory, DWMH and inhibition performance, and MTA and flexibility performance (32). The relationship between WMH and attention and executive function was also demonstrated in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Currently, significant advances have been made in neuroimaging modalities in neurodegenerative disease 12,27–29 . Neuroimaging on cognitive impairment has become a research hotspot in PD, providing in vivo insights into examining the structural and biochemical changes in PD 23,30–39 . However, no reliable predictors of cognitive impairment exist in PD so far.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is growing evidence that the WMHs is imperative to cognitive dysfunction, particularly in executive function. Niels et al reported that increasing severity of periventricular WMHs was specifically associated with impaired information processing speed and executive function ( Prins et al, 2005 ; Smith et al, 2011 ; Yamanaka et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%